Serum pepsinogen concentration as a marker of Helicobacter pylori infection and the histologic grade of gastritis ; evaluation of gastric mucosa by serum pepsinogen levels - Kiyohira, Kuninushi; Yoshihara, Masaharu; Ito, Masanori; Haruma, Ken; Tanaka, Shinji; Chayama, Kazuaki (Journal of gastroenterology, 2003)
Helicobacter pylori infection and associated gastritis are well-known significant factors in many gastrointestinal diseases, and evaluation of these conditions is important for health evaluation. We investigated the utility of serum pepsinogen (PG) concentrations for the diagnosis of H. pylori infection and evaluation of the grade of histologic gastritis. Methods: The subjects consisted of 283 individuals (147 men and 136 women; mean age, 44.0 years). Biopsy specimens were obtained from the gastric antrum and body to assess grade of inflammation and atrophy and histologic evidence of H. pylori infection. H. pylori infection was judged by Giemsa staining and serum IgG antibodies against H. pylori. PG concentrations were determined by radioimmunoassay. Results: In subjects with H. pylori infection, serum PGII concentrations were increased, and the PGI/PGII ratio (I/II ratio) was decreased. In patients with marked atrophy or intestinal metaplasia, both serum PGI and the I/II ratio were decreased. When PGII concentrations of 12 ng/ml or more, or a I/II ratio of 4.0 or less were used as the cutoff points for the diagnosis of H. pylori infection, the sensitivity and specificity of diagnosis were 90.0% and 93.5%, respectively. All subjects with serum PGI concentrations of 85 or more ng/ml, or serum PGII concentrations of 15 or more ng/ml were H. pylori-positive and all subjects with a I/II ratio of more than 6.5 were H. pylori-negative. Conclusions: These results suggest that H. pylori infection, gastritis, and glandular atrophy of the stomach can be evaluated via serum PG concentrations, allowing the evaluation of gastric mucosal integrity.